Changes in the microbiota of lamb packaged in a vacuum and in modified atmospheres during chilled storage analysed by high-throughput sequencing. (November 2016) - Wang, Taojun; Zhao, Liang; Sun, Yanan; Ren, Fazheng; Chen, Shanbin; Zhang, Hao; Guo, Huiyuan
Abstract: Changes in the microbiota of lamb were investigated under vacuum packaging (VP) and under 20% CO2 /80% N2 (LC), 60% CO2 /40% N2 (MC), and 100% CO2 (HC) modified atmosphere packaging (MAP) during chilled storage. Viable counts were monitored, and the total microbial communities were assessed by high-throughput sequencing. The starting community had the highest microbial diversity, after which Lactococcus and Carnobacterium spp. outcompeted during the 28-day storage. The relative abundances of Brochothrix spp. in the LC atmosphere were much higher than those of the other groups on days 7 and 28. The bacterial inhibiting effect of the MAP environments on microbial growth was positively correlated with the CO2 concentration. The HC atmosphere inhibited microbial growth and delayed changes in the microbial community composition, extending the lamb's shelf life by approximately 7 days compared with the VP atmosphere. Lamb packaged in the VP atmosphere had a more desirable colour but a higher weight loss than lamb packaged in the MAP atmospheres.